2015
DOI: 10.2196/mhealth.3971
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Evaluation of a Text Messaging Intervention to Support Patients With Active Tuberculosis: Implementation Considerations

Abstract: BackgroundTuberculosis (TB) remains a major global public health problem and mobile health (mHealth) interventions have been identified as a modality to improve TB outcomes. TextTB, an interactive text-based intervention to promote adherence with TB medication, was pilot-tested in Argentina with results supporting the implementation of trials at a larger scale.ObjectiveThe objective of this research was to understand issues encountered during pilot-testing in order to inform future implementation in a larger-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…From these authors 6 of the 27 platforms identified above were reported as being used in the studies. CommCare was used in 9 studies [2533], FrontlineSMS in five [16, 18, 34–36], Sana in three [37–39], Rapid SMS in two [40, 41], and one each for MoTech [42] and Magpi/DataDyne [43]. Few of the articles contained information about the advantages and disadvantages of the platform; most merely mentioned the platform and how it was used in the study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From these authors 6 of the 27 platforms identified above were reported as being used in the studies. CommCare was used in 9 studies [2533], FrontlineSMS in five [16, 18, 34–36], Sana in three [37–39], Rapid SMS in two [40, 41], and one each for MoTech [42] and Magpi/DataDyne [43]. Few of the articles contained information about the advantages and disadvantages of the platform; most merely mentioned the platform and how it was used in the study.…”
Section: Resultsmentioning
confidence: 99%
“…For FrontlineSMS, one article reported a number of advantages and disadvantages that are outline in table 3 [16], while the other three articles listing FrontlineSMS as the platform used did not report platform-specific advantages or disadvantages [18, 34, 35]. However, one set of authors described the rationale for selecting FrontlineSMS as the following: it was an open source computer-based application where researchers could log in and manage sending and receiving messages, contact information, user preferences, and passcodes; included a message database and a module to set message reminder frequency; and it supported a global system for mobile communications (GSM) modem to send and receive text messages [18].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations